The Harvard sampler : liberal education for the twenty-first century - Shephard, Jennifer M.; Kosslyn, Stephen Michael, 1948-; Hammonds, Evelynn Maxine (Harvard University Press, 2011)
From Harvard University, one of the world's preeminent institutions of liberal education, comes a collection of essays sampling topics at the forefront of academia in the twenty-first century. Written by faculty members at the cutting edge of their fields, including such luminaries as Steven Pinker, Laurel Thatcher Ulrich, and Harry R. Lewis, these essays offer a clear and accessible overview of disciplines that are shaping the culture, and even the world. The authors, among the most respected members of Harvard's faculty, invite readers to explore subjects as diverse as religious literacy and Islam, liberty and security in cyberspace, medical science and epidemiology, energy resources, evolution, morality, human rights, global history, the dark side of the American Revolution, American literature and the environment, interracial literature, and the human mind. They summarize key developments in their fields in ways that will both entertain and edify those who seek an education beyond the confines of the classroom. It is sometimes said that youth is wasted on the young. It could also be said that college, too often, is wasted on college students--that only after graduating does a former student come to appreciate learning. To those wishing to revisit the college classroom--as well as to those who never had the opportunity in the first place--this book gives a taste of the modern course at Harvard. The essays are stimulating and informative, and the annotated bibliographies accompanying each chapter provide invaluable guidance to the life-long learner who wants to pursue these fascinating topics in depth.